Induction chemotherapy followed by radiation versus concurrent chemoradiation in laryngeal cancer - Mollah, Md Nazir Uddin; Alimuzzaman, Md; Hossain, Syed Akram; Baki, Md Abdul; Nasiruzzaman, AHM; Mohammad, AKM Ghulam (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: This study was done to evaluate the effectiveness of concurrent chemo-radiotherapy than induction chemotherapy followed by radiotherapy in the loco-regional control of laryngeal cancers. Methods: This experimental study was done at Radiotherapy Department of Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from June 2004 to July 2005. Fifty three patients were selected purposively with biopsy proven squamous cell carcinoma of laryngeal region. Among the 53 patients 27 patients were treated concurrent chemo-radiation therapy and 26 patients were treated with induction chemotherapy followed by radiation. All patients were evaluated 6 weeks after completion of treatment. Results: After giving concurrent chemo-radiation complete response occurred in 74% and partial response occurred in 26% patients but after giving induction chemotherapy followed by radiotherapy, complete response occurred in 23% and partial response occurred in 77% patients. Conclusion: Concurrent chemo-radiation is more effective than induction chemotherapy followed by radiotherapy. Key words: Laryngeal cancer; radiotherapy; chemotherapy. DOI: 10.3329/bjo.v16i2.6833 Bangladesh J Otorhinolaryngol 2010; 16(2): 86-90